Failure of Orthopaedic Residents to Voluntarily Participate in a Laboratory Skills Training. Issue 4 (15th February 2022) - Hill, Jared J.; Gulbrandsen, Trevor R.; Wynn, Malynda S.; Anderson, Donald D.; Thomas, Geb W.; Marsh, J. Lawrence; Karam, Matthew D.
Abstract : Introduction: Arthroscopy simulation is increasingly used in orthopaedic residency training. The implementation of a curriculum to accommodate these new training tools is a point of interest. We assessed the use of a high-fidelity arthroscopy simulator in a strictly voluntary curriculum to gauge resident interest and educational return. Methods: Fifty-eight months of simulator use data were collected from a single institution to analyze trends in resident use. Comparable data from two additional residency programs were analyzed as well, for comparison. Orthopaedic residents were surveyed to gauge interest in continued simulation training. Results: Average annual simulator use at the study institution was 27.7 hours (standard deviation = 26.8 hours). Orthopaedic residents spent an average of 1.7 hours practicing on the simulation trainer during the observation period. A total of 21% of residents met or exceeded a minimum of 3 hours of simulation time required for skill improvement defined by literature. Most (86%) of the residents agreed that the simulator in use should become a mandated component of a junior resident training. Conclusion: Although surgical simulation has a role in orthopaedic training, voluntary simulator use is sporadic, resulting in many residents not receiving the full educational benefits of such training. Implementation of a mandated simulation training curriculum is desired by residents and could improve the educational return of surgical simulators in residency training.